Synovial Histiocytic Sarcoma in a Dog - Radiographic, Ultrasonographic and Elastographic Findings - Tinto, Stéfany Tagliatela; Ramos, Denise Jaques; Evangelista, Gabriela Castro Lopes; De Macedo, Erick Ewdrill Pereira; Assada, André Nito; Freitas, Silvio Henrique; Strefezzi, Ricardo de Francisco; Antônio Rossi Feliciano, Marcus (Acta Scientiae Veterinariae, 2024)
Background: Histiocytic sarcoma is a malignant tumor that commonly affects large-breed, middle-aged dogs in the form of solitary masses that may affect joints and other organs. The imaging findings (radiography, ultrasound and elastography) of synovial histiocytic sarcoma correlated with cytological, histopathological and immunohistochemical tests are still poorly described in the veterinary literature. The aim of this report was to describe the main imaging findings of an articular histiocytic sarcoma on radiography, B-mode ultrasound and shear wave elastography and to correlate them with cytology, histopathology, and immunohistochemistry tests. Case: A 7-year-old castred male Rottweiler was referred to the Veterinary Hospital (HOVET) of the Universidade de São Paulo (USP, Pirassununga campus) with the main complaint of pain and increased volume in the left thoracic limb in the region of the elbow joint. The animal received a physical examination, including palpation of the volume enlargement, which had an irregular, verrucous appearance and painful sensitivity on palpation. In order to assess the extent of the lesion and the involvement of the elbow joint, the patient was referred to the imaging department for imaging tests. The radiography revealed a lytic and proliferative bone lesion that could be of inflammatory, neoplastic, or degenerative joint disease origin. The animal was referred for cytological examination to clarify the case, which characterized the lesion as an active chronic inflammatory process. The ultrasound revealed areas of heterogeneous echotexture interspersed with anechogenic areas in the periarticular and articular regions. The areas identified by ultrasound were stained red on the color elastogram by qualitative elastography. The quantitative elastography showed an average shear wave velocity of approximately 2.80 m/s in the ROI. The elastographic examination demonstrated high tissue stiffness, which is indicative of malignancy. Based on these results, the patient was referred for bone biopsy and samples were collected for histopathologic and immunohistochemical examination. The examinations characterized the increase in volume as a synovial histiocytic sarcoma. Discussion: The aim of this report was to highlight the fundamental role of shear wave elastography in the evaluation of tumors and periarticular volume increases as a predictor of malignancy. The report described the main imaging findings of an articular histiocytic sarcoma on radiography, B-mode ultrasound, and shear wave elastography. The radiographic findings of the patient were consistent with lytic and proliferative bone lesions. Shear wave elastography was performed as a way of predicting the malignancy of the lesion and confirm the cytological finding of an inflammatory lesion. It played a fundamental role in assessing the stiffness of the mass. In this case, the qualitative and quantitative characteristics indicated that it was a malignant process. Strain and shear wave elastography can therefore be established as a diagnostic tool to help reduce the misclassification of histiocytic sarcoma and other tumors. Veterinarians can refer samples with high wave velocity values and a reddish color elastogram to the most recommended tests for diagnosing malignant tumors, which will allow for the most appropriate therapy to be instituted. This report was able to combine radiographic, ultrasound and elastographic findings to characterize an articular histiocystic sarcoma as completely as possible. Keywords: histiocytic sarcoma, imaging , dog, elastography.